Application of model-based LPV actuator fault estimation for an industrial benchmark. (November 2016) - Chen, Lejun; Patton, Ron; Goupil, Philippe
Abstract: To bridge the gap between model-based fault diagnosis theory and industrial practice, a linear parameter varying H − / H ∞ fault estimation approach is applied to a high fidelity nonlinear aircraft benchmark. The aim is to show how the fault estimation can provide robust early warning of actuator fault detection scenarios that can lead to abnormal aircraft flight configurations. The fault estimator state space solution is parameterised a priori using parameter-independent design freedom. Following this only constant free matrices are determined and the resulting affine linear parameter varying estimator has low computational load. The evaluation uses parametric simulation via an industry standard Monte Carlo campaign supported by a functional engineering simulator. The simulations are carried out in the presence of aerodynamic database uncertainties and measurement errors covering a wide range of the flight envelope. Abstract : Highlights: Bridging the gap between the model-based FDI theory and the demands from the aerospace industry. Estimating actuator faults in both local and global system levels. H − / H ∞ Estimator gains are parameterized using free matrices, which results in a low computational load. The Monte-Carlo verification and validation (V&V) campaign of FDI scheme is presented.